Komercjalizacja i prywatyzacja placówek ochrony zdrowia w Polsce a globalny rynek usług medycznych - Węgrzyn, Maria (Commercialization and Privatization of Health Care Units in Poland and the Global Market of Medical Services, 2006)
System changes dropping in Poland in 90-ties influenced the trend of transformations and development of the health care system in the meaning way. Dissatisfaction of patients from the quality of given services and ineffectiveness of existing medical posts have caused the need to search for better form of operation in this sector. Present actions directed to the privatization and commercialization are pointing at potentially better economic efficiency of transformed subjects. The announced process of private transformations will be happening in Poland on the background of uniting Europe. So the author is showing the threats and benefits that the globalization process is causing in regard to medical companies, in particular of small or average entities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 15-28